PENGARUH HOAX DI MEDIA SOSIAL TERHADAP PREFERENSI SOSIAL POLITIK REMAJA DI SURABAYA - Dinda Marta Almas Zakirah (Mediakita, 2020)
Easy access to social media has several impacts that can harm others. Irresponsible people are now abusing the freedom of expression, for example, the spread of fake news or hoaxes. Even though the government has made regulations and threats, it does not provide a deterrent effect for the perpetrators. This hoax news is intentionally created to influence or change the perception of readers. Surabaya is one of the cities where the majority of the population has access to social media, especially for today's youth. This study focuses on how hoax news on social media affects the mindset of adolescents in Surabaya and how adolescents respond to hoax news in social media. This study uses a qualitative method with Habermas's public space theory approach. The results showed that the emergence of hoax news can influence the views of Surabaya teenagers regarding the object being reported, then when spreading fake news or hoaxes, they do not do editing first, and there are several factors that influence teenagers to spread fake news, namely, for fun, share information and think that the news obtained is important news for other readers.